Local executives' perceptions and initiatives for reinventing local government towards the Philippine 2000 vision - Sajo, Thomas A.; Tabaldo, Lilia E. (1994)
This paper highlights the set of strategies recommended to enhance devolution of maternal and child health services under the 1991 Local Government Code of the Philippines. The strategies hope to ensure the application of an integrated model of development through the implementation of such strategies as: multilateral/multisectoral, minimum basic needs, focused targeting, social mobilization, community-based approach, capability- building, setting up a community- based information system and measures to enhance local financial management.
Keywords: Local autonomy; Management of local government; Local government laws; Decentralization in government